Comparison between the commonly used radiographic techniques for intra oral imaging in dentistry-A questionnaire study - Tatapudi, Ramesh; Myla, Swathi; Gurugubelli, Upendra; Koneru, Jyothirmai; K, Meenakshi; Bandaru, Sravani; Thumula, Reshmi (International Journal of Dental Research, 2017)
Aim:-To compare the opinion regarding usage of bisecting-angle technique and the paralleling techniques among BDS students, post graduate students, private practitioners in and around Bhimavaram town for intra oral imaging in dentistry. Materials and methods: A detailed questionnaire composed of questions regarding technical parameters, exposure parameters, operator and patient comfort and image accuracy in diagnosis. Details of the study were explained to the participants preferred option to be marked according to the question mentioned in the questionnaire. Total 500 individuals participated in the present study, with 100 individuals in each group. Data was collected and entered in Microsoft Excel (2010) and statistically analysed using SPSS 20. Chi-square test was used to evaluate differences in the responses with P-value ≤ 0.05 were considered significant. Results: Results showed that in technical parameters most of the people opted for bisecting angle technique with p value≤ 0.05 and found as significant. In aspect of exposure parameters, results are in favour of paralleling technique and p value is ≤ 0.05. In aspect of the operator and patient comfort there is an equal opinion most of them opted for bisecting angle technique and paralleling technique p value is significant. In aspect of image accuracy p value is significant for paralleling technique. Conclusion: Great work should have to be done to alleviate the quality of radiographs and the understanding and perspective of dental graduates regarding dental and maxillo-facial radiology. The results of present study revealed though there is knowledge about the techniques, but lack of application decreases their ability to get more accurate diagnostic radiograph. Paralleling technique being the most accurate in image accuracy should be emphasized to practice and needed to be modified in conditions where it is not feasible to deal with.